2016
DOI: 10.1007/s12665-016-5440-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar application on Suaeda salsa growth and saline soil properties

Abstract: Pot experiments were conducted to study the effects of biochar application rates (5, 10, 20 g/kg) and types of wheat straw biochar (WS), corn stalk biochar (CS) and peanut shell biochar (PS) on Suaeda salsa (S. salsa) growth and properties of saline soil in Yellow River Delta. It was found that S. salsa yield increased from 11.7 to 115 % under WS application at a range of 5-10 g/kg compared with control. As biochar rate increased to 20 g/ kg, the increment decreased to 102 %. The underground biomass of S. sals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 35 publications
3
23
0
2
Order By: Relevance
“…Proportional to biochar application rate CEC increased linearly in treatments T1, T3 and T5. This phenomenon was also stated by Sun et al (2016) when applied wheat straw biochar at different rates (5, 10 and 20 g/kg) to saline soil in Yellow River Delta. Similar trends were observed in other studies and reports (Glaser et al 2002;Rondon et al 2007;Blackwell et al 2010;Van Zwieten et al 2010;Ullah et al 2018).…”
Section: Soluble and Exchangeable Cations And Cecsupporting
confidence: 64%
“…Proportional to biochar application rate CEC increased linearly in treatments T1, T3 and T5. This phenomenon was also stated by Sun et al (2016) when applied wheat straw biochar at different rates (5, 10 and 20 g/kg) to saline soil in Yellow River Delta. Similar trends were observed in other studies and reports (Glaser et al 2002;Rondon et al 2007;Blackwell et al 2010;Van Zwieten et al 2010;Ullah et al 2018).…”
Section: Soluble and Exchangeable Cations And Cecsupporting
confidence: 64%
“…The application of organic amendments in SAS is considered a useful and effective way to increase soil fertility and enhance crop growth [31,157]. The application of organic amendments in SAS increased the biomass yield of alfalfa, Medicago sativa [182]; barley, Hordeum vulgare [31]; cotton, Gossypium hirsutum [143]; maize, Zea mays [32,159,183]; onion, Allium cepa [142]; rice, Oryza sativa [31,153,184]; seepweed, Suaeda salsa [185]; sweet fennel, Foeniculum vulgare [186]; tomato, Solanum lycopersicum [187]; and wheat, Triticum aestivum [139]. The quantitative and qualitative improvements in the growth and yield attributes of crops as affected by abiotic stresses in the presence of different additives might be due to the enhanced photosynthesis, cholorophyll contents, stomatal conductance, water-use efficiency, and synthesis of metabolites [137,[188][189][190][191].…”
Section: Effects Of Organic Amendments On the Physical Chemical Andmentioning
confidence: 99%
“…Recent studies on the negative effect of high BC application on soil-plant system revealed that addition of BC at levels of 10, 20 and 30 t ha -1 produced positive influence on grain yield of winter rye, with 20 t ha -1 resulting in the highest grain yields (Kraska et al, 2016). Pot experiments revealed that S. salsa yield increased from 11.7 to 115% with WS application in the range of 5-10 g kg -1 , when compared with control (Sun et al, 2016). However, as BC level increased to 20 g kg -1 , the yield decreased to 102%.…”
Section: Discussionmentioning
confidence: 98%